COLOR INTENSITY AND ANTIOXIDATIVE CAPACITY OF FOUR NATURAL MONOFLORAL HONEY FROM MALDA, INDIA - SURAJIT ROY; SHYAMAPADA MANDAL (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to explore the color intensity and antioxidative capacity of mango honey available from local niches, in and around Malda, West Bengal, India. Methods: Four mango honey samples: LMH1, LMH2, LMH3, and LMH4, were collected from bee hives, in and around Malda, India, and were subjected to determine the color intensity and antioxidative capacity in 2, 2-diphenyl-1-picrylhydrazyl system. Results: The honey samples tested had light to dark color variation with color intensity values of 583.59–1842.84 mAU. The total phenolic content (TPC) of the honey samples ranged from 434.52 to 1450.74 μg gallic acid equivalents/ml, while the total flavonoids content (TFC) ranged 39.4–72.67 mg quercetin equivalents/100 g of honey. The honey samples displayed antioxidative activity (AOA) with 9.91–76% inhibition capacity, and the IC50 values of 8.37–19.38 mg/ml. The color intensity of test honeys displayed positive correlation with the TPC (r=0.907) and TFC (r=0.863), while negative correlation between honey color intensity and IC50 values (r=−0.955) was recorded. Conclusion: The locally available mango honeys were rich in bioactive components displaying excellent AOA, and thus, the native honey might be utilized as the potential source of natural antioxidant in our part of the globe.